1993
DOI: 10.1037/0021-9010.78.4.602
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of children's self-esteem through social support training for youth sport coaches.

Abstract: The authors examined the impact of coaching behaviors on players' self-enhancement processes. Eight baseball coaches attended a preseason workshop designed to increase their supportiveness and instructional effectiveness. Behavioral guidelines were presented and modeled. A no-treatment control group had 10 coaches. Boys (N = 152) in both groups were interviewed pre- and postseason. Trained coaches differed from controls in player-perceived behaviors in accordance with the guidelines. They were evaluated more p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
134
0
4

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 221 publications
(154 citation statements)
references
References 29 publications
13
134
0
4
Order By: Relevance
“…Findings from a study of social support training for coaches showed that players whose coaches participated in the two and a half hour training had more fun during the season and gave their coaches higher ratings than players whose coaches did not receive the same training (Smoll, Smith, Barnett, & Everett, 1993). The same study also found that boys with low self-esteem who played for the trained coaches experienced significant self-esteem growth over the course the season in comparison to the control group.…”
Section: Sportssupporting
confidence: 61%
“…Findings from a study of social support training for coaches showed that players whose coaches participated in the two and a half hour training had more fun during the season and gave their coaches higher ratings than players whose coaches did not receive the same training (Smoll, Smith, Barnett, & Everett, 1993). The same study also found that boys with low self-esteem who played for the trained coaches experienced significant self-esteem growth over the course the season in comparison to the control group.…”
Section: Sportssupporting
confidence: 61%
“…A series of 12 singleitem measures of behaviors (Smith, Smoll, & Barnett, 1995;Smith, Smoll, & Curtis, 1979;Smoll, Smith, Barnett, & Everett, 1993) assessed reactive and spontaneous behaviors corresponding to the Coaching Behavior Assessment System (CBAS; Smith, Smoll, & Hunt, 1977): reinforcement, nonreinforcement, encouragement after mistakes, mistake-contingent technical instruction, punishment, punitive technical instruction, ignoring mistakes, keeping control, general technical instruction, general encouragement, organization, and general communication. Participants rated the frequency with which their coach demonstrated the behavior described in each item on a scale ranging from 1 (never) to 7 (almost always).…”
Section: Instrumentsmentioning
confidence: 99%
“…Furthermore, these volunteer coaches typically do not have formal coaching training even though research has shown that teams with coaches trained in positive coaching retain almost all (95%) of youth sport participants, whereas untrained coaches retain only 73% each year (Barnett, Smoll, & Smith, 1992). As well, research has consistently found that such training resulted in a more positive experience for youth sport participants which in turn increased their self-esteem and sport enjoyment (Smoll, Smith, Barnett, & Everett, 1993).…”
mentioning
confidence: 99%